Optimalisasi Standar Pelayanan Minimum Mass Rapid Transit (MRT) - Sevia Dwi Astuti; Tiara Nur Angraini; Ikram Maulana Firdaus; Taufik Nurochman (Universitas 17 Agustus 1945 Semarang, 2023)
This research was conducted at PT MRT Jakarta which is a fast rail transportation system in Jakarta. This study aims to determine the optimization of MRT Jakarta's minimum service standards and its relation to customer satisfaction. This study uses a qualitative method with data collection through questionnaires, and literacy studies related to supporting documents at PT MRT Jakarta. Based on the research results of PM 47 of 2014, it shows that the five indicators such as tangible, reliability, responsiveness, assurance, and empathy provided by PT MRT Jakarta are effective and in accordance with the SOP.